2016
DOI: 10.1097/md.0000000000005602
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and prognosis in women with breast cancer

Abstract: Background:Diabetes mellitus is associated with an increased risk of breast cancer, but studies of the effects of diabetes on the prognosis of women with breast cancer have yielded inconsistent findings. The present meta-analysis aimed to investigate the impact of preexisting diabetes on the prognosis in terms of overall survival (OS), disease-free survival (DFS), and relapse-free period (RFP) in women with breast cancer.Methods:We searched the Embase and PubMed databases until June 2016 for cohort or case–con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 38 publications
(46 reference statements)
5
68
0
3
Order By: Relevance
“…In another study based on SEER-Medicare data, women diagnosed with diabetes prior to breast cancer diagnosis had a higher all-cause mortality compared with women without diabetes 20 . In a meta-analysis of seventeen studies, pre-existing diabetics were shown to have a 50% higher all-cause mortality than those without diabetes 21 . To the best of our knowledge, the association between diabetes diagnosed at or after breast cancer diagnosis and survival has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In another study based on SEER-Medicare data, women diagnosed with diabetes prior to breast cancer diagnosis had a higher all-cause mortality compared with women without diabetes 20 . In a meta-analysis of seventeen studies, pre-existing diabetics were shown to have a 50% higher all-cause mortality than those without diabetes 21 . To the best of our knowledge, the association between diabetes diagnosed at or after breast cancer diagnosis and survival has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, similarly, because of a limited sample to analyze RFS, no sufficient evidence of a significant difference in RFS between patients with and without DM was observed. DM is also independently correlated with poor prognosis in patients with various cancers, such as pancreatic cancer, renal cell carcinoma, and breast cancer . These results suggest that DM is an independent unfavorable prognostic factor for NSCLC after surgical resection.…”
Section: Discussionmentioning
confidence: 67%
“…DM is also independently correlated with poor prognosis in patients with various cancers, such as pancreatic cancer, 31 renal cell carcinoma, 32 and breast cancer. 33 These results suggest that DM is an independent unfavorable prognostic factor for NSCLC after surgical resection. As a result, surgically treated NSCLC patients with DM might benefit from better glucose control and closer postoperative follow-up.…”
Section: Discussionmentioning
confidence: 77%
“…Meta-analyses have shown that diabetes mellitus is a risk factor for the development of breast cancer 27 , and that diabetes mellitus is associated with a poorer prognosis in women who develop breast cancer 12,13 . The most recent meta-analysis was published in 2016, including 17 studies and 48,315 women with breast cancer; the results showed that the pooled aHR for poorest overall survival was 1.51, and 1.28 for poorest disease-free survival in patients with diabetes mellitus in comparison with those without diabetes mellitus 13 . In addition, Tsilidis et al 28 carried out an "umbrella review" of meta-analyses of observational studies examining the relationship of diabetes mellitus and cancer, and suggested that only a minority of studies reporting a link between diabetes mellitus and various cancers had "robust" supporting evidence without bias.…”
Section: Discussionmentioning
confidence: 99%